The Influence of the Work Environment on Teacher Performance at Early Childhood Education Puri Amanah Klari Karawang - Jayanti, Thursina Della; Mulyani, Sri; Fauzobihi, Fauzobihi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze the influence of work environment on teacher performance at PAUD Puri Amanah Klari Karawang. The research method used a quantitative approach with descriptive-associative design involving 30 teachers as respondents through total sampling technique. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis used descriptive statistics and simple linear regression with statistical software assistance. The results showed that work environment significantly influenced teacher performance with a significance value of 0.623 > 0.05 and regression coefficient of 0.023. The R² value of 0.009 indicates that work environment contributes 0.9% to teacher performance, while 99.1% is influenced by other factors such as motivation, competence, and leadership. Respondent characteristics were dominated by women aged 21-30 years with S1 qualifications and 5-6 years of work experience. This research provides implications for the importance of optimizing work environment as a basic foundation for improving teacher performance in achieving quality early childhood education goals.